LEVELS OF EVIDENCE AND GRADES OF RECOMMENDATIONS IN HSCT AND CELLULAR THERAPY - Arcuri, Leonardo Javier (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION